Batik Coloring With Gambir Waste: Reduction of Quantity and Soaking Length on Color Intensity - Efi, Agusti; Muthia, Gabila Heira; Nelmira, Weni; ., Hadiastuti; Zamil, Ilham; Aryati, Yulia; Munaf, Yuniarti; Akmal, Ahmad; Novaliendry, Dony (Journal of Ecohumanism, 2024)
Natural dyes are increasingly important as an alternative to synthetic dyes because they are more environmentally friendly and not harmful to health. Gambirr liquid waste, a by-product of gambirr production, has potential as a natural dye for batik. This research aims to test the effect of quantity and duration of soaking mori in gambirr waste solution on color intensity and the application of gambirr waste in making batik crafts. The research uses a creative experimental method with a design process approach. The quantity of gambirr waste, soaking time, and use of fixator (alum, tunjung, whiting) were tested to assess their effect on color intensity. Procedures include mori dipping, color fixation, and color streaking. The results showed that the quantity of gambirr waste and the soaking time significantly influenced the color intensity of the mori. A more intense color is produced with a higher solution concentration and longer soaking until it reaches the saturation point. The use of a fixator produces different color variations, strengthening the color’s resistance to fading. Gambir liquid waste has been proven to be effective as a natural dye with variations in color intensity based on quantity, time and fixator settings. Factors such as pH, temperature, and dyeing technique also influence the results. This research contributes to efforts to sustain and innovate environmentally friendly batik art.